The Aggada of the Bavli and its cultural world - Herman, Geoffrey; Rubenstein, Jeffrey L. (Brown Judaic Studies, 2018)
"The Babylonian Talmud, the great compilation of Jewish law edited in the seventh century CE, also contains a great deal of aggada, that is, non-legal material, including interpretations of the Bible, stories, folk sayings and prayers. The Talmud's aggadic traditions contain echoes of the conversations with the surrounding cultures of the Persians, other Iranian peoples, Eastern Christians, Manichaeans, Mandaeans, and the ancient Babylonians. The essays in this volume analyze Bavli aggada to reveal this rich engagement of the Talmud and its cultural world"--